Effects of frozen storage, radiation and their combined Treatments on microorganisms of freshwater mola fish Amblypharyngodon mola (Journal of Bangladesh Academy of Sciences, 2013)
The study revealed that the total viable bacterial count, staphylococcal count, coliform count, faecal coliform count, Aeromonas count and total fungal counts varied from 8.8×107 to 1.27×108, 2.7×106 to 4.2×106, 9.0×104 to 1.03×105, 4.8×105 to 7.3×105, 2.7×105 to 5.0×105 and 1.6×103 to 3.5×103 cfu/gm, respectively. Seventy six bacterial strains were isolated and identified, where Staphylococcus aureus, Micrococcus varians, Aeromonas hydrophila, Klebsiella ozaenae, Bacillus subtilis, Escherichia coli, Bacillus megaterium, Klebsiella edwardsii, Pseudomonas aerugenosa and Micrococcus radiodurans were 16 (21.06%), 11 (14.47%), 9 (11.82%), 6 (7.89%), 6 (7.89%), 8 (10.53%), 6 (7.89%), 4 (5.26%), 7 (9.21%) and 3 ( 3.95% ), respectively. Total coliform, faecal coliform, Aeromonas bacteria and total fungi were found to be totally inactivated by the irradiation dose of 2.5 kGy onwards and total viable bacteria and staphylococcal bacteria were eliminated completely at the irradiation dose of 7.5 kGy. The bacterial counts were shown to be gradually decreased in all the samples from initial to final storage. The combined treatments were found more effective than that of the single treatment for reducing or eliminating the associated bacteria. The moisture contents of the studied fish were found nearly similar during initial and final storage periods and also at different radiation doses but the total protein contents decreased during final storage period and also at different radiation doses. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15677 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 21-31, 2013